The problems and perspective for appreciates if bred-making quality of wheates the different generations sorts - О. І. Шевченко; Л. О. Турченюк (Plant Varieties Studying and Protection)
It has been supposed to carry out bred-making valuation of wheat under native condition of protein substances and contents of the dough improvers (КВrO3, С6Н8О6) being practiced. It will allow both at present and in the future to carry out comparative valuation by this index between varieties of various breeding progenies.